Failure behaviors of oriented strand board material under quasi-static and dynamic loads - Meng, Qingfei; Chen, Wensu; Hao, Hong; Cui, Jian; Shi, Yanchao; Zhang, Xuejie (American Society of Civil Engineers (ASCE), 2018)
© 2017 American Society of Civil Engineers. Oriented strand board (OSB) is an engineering material used in the building industry. In lieu of its cost-effectiveness and sustainability, OSB has been used widely as the skin layer of structural insulated panel (SIP), and is usually used in the building as wall panel and roof panel. During its service life, such panels might be subjected to various dynamic loads, such as windborne debris impact. Good understanding of dynamic failure behaviors of OSB material at different strain rates is needed for reliable prediction of the performance of OSB panel under dynamic loading. In this study, quasi-static and dynamic tests were carried out to investigate the static and dynamic failure behaviors of a specific OSB material. The testing results indicated the tensile strength of OSB was sensitive to strain rate. The damage mode under quasi-static loading condition was found to be different from that under dynamic loading condition, which affected the tensile strength of OSB material. An empirical formula was derived to predict the tensile strength enhancement of OSB material under different strain rates based on the testing results.